TRANSFORMASI NOVEL PEREMPUAN BERKALUNG SORBAN KE DALAM FILM PEREMPUAN BERKALUNG SORBAN: KAJIAN EKRANISASI - Dede Irawan; Harris Effendi Thahar; Muhammad Ismail Nasution (Jurnal Bahasa dan Sastra, 2013)
The purposes of this research are (1) describe the reduction of the story of the novel Perempuan Berkalung Sorban which was adapted into a movie entitled Perempuan Berkalung Sorban, (2) describe the addition of the story of the movie Perempuan Berkalung Sorban which was adapted from the novel Perempuan Berkalung Sorban, (3) describe various form of changing or alterations of the novel Perempuan Berkalung Sorban which was adapted into the movie Perempuan Berkalung Sorban, (4) describe the function of alterations of the novel Perempuan Berkalung Sorban which has been adapted into the movie Perempuan Berkalung Sorban. Data of this research are parts of the story in the novel and movie Perempuan Berkalung Sorban which shows the reduction, addition, and various alterations that is measured from the novel Perempuan Berkalung Sorban. Sources of the data are the novel and movie Perempuan Berkalung Sorban. The data were taken through notetaking method. Research findings shows that there are 24 events, 9 characters, and 5 settings.